2016
DOI: 10.1186/s12890-016-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin bronchoscopy for solitary pulmonary lesions in a region endemic for tuberculosis: a randomised pilot trial

Abstract: BackgroundThe evaluation of solitary pulmonary lesions (SPL) requires a balance between procedure-related morbidity and diagnostic yield, particularly in areas where tuberculosis (TB) is endemic. Data on ultrathin bronchoscopy (UB) for this purpose is limited. To evaluate feasibility and safety of UB compared to SB for diagnosis of SPL in a TB endemic region.MethodsIn this prospective randomised trial we compared diagnostic yield and adverse events of UB with standard-size bronchoscopy (SB), both combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
(27 reference statements)
0
13
1
Order By: Relevance
“…The diagnostic yields of the UTB and the standard‐size bronchoscope were 55.0% and 80.0%, respectively ( p = 0.18). In that study, UTB was not superior to standard‐size bronchoscopy for the evaluation of PPLs when combined with fluoroscopic guidance because of the limitations of the small, 1.2‐mm working channel, which limited the ability to sample specimens and had poor suction capability 32 . Currently available UTBs share this limitation; however, the novel UTB used in the present study has a 1.7‐mm working channel that is able to accommodate a wider variety of bronchoscopic instruments, including a 1.5‐mm biopsy forceps, which is an important feature for the diagnosis of PPLs.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnostic yields of the UTB and the standard‐size bronchoscope were 55.0% and 80.0%, respectively ( p = 0.18). In that study, UTB was not superior to standard‐size bronchoscopy for the evaluation of PPLs when combined with fluoroscopic guidance because of the limitations of the small, 1.2‐mm working channel, which limited the ability to sample specimens and had poor suction capability 32 . Currently available UTBs share this limitation; however, the novel UTB used in the present study has a 1.7‐mm working channel that is able to accommodate a wider variety of bronchoscopic instruments, including a 1.5‐mm biopsy forceps, which is an important feature for the diagnosis of PPLs.…”
Section: Discussionmentioning
confidence: 93%
“…Franzen et al conducted a small pilot study comparing bronchoscopy using a conventional 2.8-mm ultrathin bronchoscope with a 1.2-mm working channel to standardsize bronchoscopes with external diameters of 5.0-6.0 mm for diagnosing PPLs in a region endemic for tuberculosis (32). Forty patients were enrolled and assigned to either ultrathin or standard-size bronchoscope groups, of whom 28% were ultimately diagnosed with tuberculosis.…”
Section: Randomized Trials Among Bronchoscopes Of Different Sizesmentioning
confidence: 99%
“…Other Authors reported on the utility of cytological specimens containing typical granulomas collected through fluoroscopicallyguided brushing and transbronchial needle aspiration in the diagnosis of TB-related peripheral pulmonary nodules and masses (Tamura et al, 2010;Reichenberger et al, 1999;Gasparini et al, 1995;Jafari et al, 2013;Franzen et al, 2016) (Figure 1). Franzen et al, who carried out a randomized controlled trial in a high TB incidence country, failed to demonstrate a higher yield of brushing and TBLB performed with an ultrathin bronchocope versus samplings obtained with a standard bronchoscope (Franzen et al, 2016).…”
Section: Transbronchial Biopsy Techniquesmentioning
confidence: 99%